Potential Antioxidant Kombucha Fortified with Balinese Salak Juice (Salacca zalacca Var Amboinensis) From Karangasem District - Ida Ayu Putu Ary Widnyani; Wahyu Krisna Yoga; Putu Rima Sintyadewi; Ni Komang Sri Ariani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Salak (Salacca zalacca Var. Amboinensis) is widely spread in Indonesia. Processing salak using fermentation method can provide added value and extend the shelf life. Fermented salak product combined with kombucha from balck tea is expected to increase the product’s ability to inhibit free radicals and provide healthful effects for health, especially the digestive process. This research endeavors to assess the capacity and antioxidant activity (IC50) from the product. The data that has been obtained was analyzed statistically using a completely randomized two-factor design. The first factor involves the ratio of salak extract to black tea, featuring three levels 80:20 ; 70:30 ; 60:40. The second factor encompasesses varying fermentation duration with four levels 4,8,12, and 16 days fermentation. The experiment was replicated three times. The result is that the comparison of salak extract with black tea had an antioxidant capacity between 101,37-479,30 GAE/100g. The result for antioxidant activity (IC 50) between 97,77-179,61 ppm.